Integrated Compliance Framework for Holding and Subsidiaries Company to Protecting Corporate Value and Sustainability - Agustin Tri Setyoningsih; Utomo Sarjono Putro (Journal Integration of Management Studies, 2025)
This research aims to develop an integrated compliance framework designed to protect corporate value and sustainability for a State-Owned Holdings and Subsidiaries in the chemical sector. Utilizing qualitative research methods such as semi structured interviews, internal and external document reviews, SWOT analysis, Root Cause Analysis, comparative benchmarking with a state owned holding company in the energy sector, Business Process Integration (BPI), and Business Process Reengineering (BPR), the research aligns its framework with the State Owned Enterprise regulation PER-2/MBU/03/2023 and the ISO 37301:2021 compliance standard. The research findings identify significant gaps in compliance structures, processes, and outcomes caused by unclear definitions of roles and responsibilities, inadequate compliance staffing, fragmented business processes, and insufficient digital integration. To address these issues, the research proposes strategic recommendations including the centralization of compliance structures, standardization of processes, integration of digital compliance platforms, and the establishment of clear compliance performance indicators and maturity measures. This research contributes a structured and actionable plan leveraging BPR and BPI methodologies to clearly define responsibilities and operational steps, ensuring effective compliance integration between holding and subsidiary companies, thereby enhancing compliance effectiveness and safeguarding corporate sustainability and value.